A Survey on Comparative Study of Customer Behaviour in Online and Offline Purchase of Electronic Items in Ahmedabad - Khan, Arbaz; Makwana, Anjali; Vidani, Jignesh (MultiTech Publisher, 2023)
Online shopping is quite a new thing these days, although some people are still unaware of it. Although everyone uses the word